Induction of angiogenesis by normal and malignant plasma cells - Hose, Dirk; Moreaux, Jérôme; Meißner, Tobias; Seckinger, Anja; Goldschmidt, Hartmut; Benner, Axel; Mahtouk, Karène; Hillengaß, Jens; Rème, Thierry; De Vos, John; Hundemer, Michael; Condomines, Maud; et al. (Blood, 2009)
Abundant bone marrow angiogenesis is present in almost all myeloma patients requiring therapy and correlated to treatment response and survival. We assessed the expression of 402 angiogenesis-associated genes by Affymetrix DNA microarrays in 466 samples, including CD138-purified myeloma cells (MMCs) from 300 previously untreated patients, in vivo microcirculation by dynamic contrast-enhanced magnetic resonance imaging, and in vitro angiogenesis (AngioKit-assay). Normal bone marrow plasma cells (BMPCs) express a median of 39 proangiogenic (eg, VEGFA, ADM, IGF-1) and 28 antiangiogenic genes (eg, TIMP1, TIMP2). Supernatants of BMPCs unlike those of memory B cells induce angiogenesis in vitro. MMCs do not show a significantly higher median number of expressed proangiogenic (45) or antiangiogenic (31) genes, but 97% of MMC samples aberrantly express at least one of the angiogenic factors HGF, IL-15, ANG, APRIL, CTGF, or TGFA. Supernatants of MMCs and human myeloma cell lines induce significantly higher in vitro angiogenesis compared with BMPCs. In conclusion, BMPCs express a surplus of proangiogenic over antiangiogenic genes transmitting to the ability to induce in vitro angiogenesis. Aberrant expression of proangiogenic and down-regulation of antiangiogenic genes by MMCs further increases the angiogenic stimulus, together leading to bone marrow angiogenesis at various degrees in all myeloma patients.
Prebulished online as Blood first edition paper, March 18, 2009
Gesehen am 14.01.2022